Pengalaman Pasien Diabetes Mellitus yang Tinggal Sendiri dalam Melakukan Manajemen Diri - Sovia Susianty; Mahathir Mahathir; Fitri Mailani; Hema Malini; Chong Mei Chan (Ners Jurnal Keperawatan, 2021)
Self-management is an important component that will be integrated into the daily activity patterns of people with Diabetes Mellitus (DM) to regulate blood glucose levels, reduce symptoms, and prevent complications. DM patients who live alone will face challenges and self-efficacy in self-management. The purpose of this study was to explore the experience of diabetes mellitus patient living alone in self management performance. Qualitative research design, a phenomenological study was used in this study. The number of participants was six,  namely solitaire DM who have been diagnosed with DM for more than 1 year,  able to communicate well. The technique of taking participants was using purposive sampling  according to inclusion criteria. The main instrument is the researcher himself. Collecting data with in-depth interviews, observations and field notes. Data analysis using Colaizzi's method begins with making transcripts, determining categories, formulating sub-themes and themes. This study generaten 6 themes, namely diet management, experience of antidiabetic treatment, herbal treatment as the main choice, modification of physical activity around the house, blood sugar monitoring and personal wisdom in controlling blood sugar. proper use of antidiabetic drugs and herbal remedies. Implementation of home visits for DM sufferers who live alone can increase understanding of the use of antidiabetic drugs and appropriate herbal remediesKeywords: Diabetes Mellitus, Self Management, Solitaire